Novel extraction process method for purifying germanium tetrachloride - ZHOU JIAJUN; LIU YUE; WANG YANG (2010)
The invention discloses a novel extraction process method for purifying germanium tetrachloride. Purification is the subject of the germanium metallurgical industry. The method is combined with an extraction theory, and a novel germanium tetrachloride purification process is researched through experiments. The dissolving situations of substances such as AsCl3 and the like in hydrochloric acid and GeCl4 differ greatly, and the aim of purifying GeCl4 can be fulfilled by extracting substances such as AsCl3 and the like in crude GeCl4 by taking the hydrochloric acid as an extracting agent. Conventional extraction is used for extracting active ingredients in a mixture. In recent years, an extraction method is used for purification. Full and effective mixing of the extracting agent and an extracted substance is a relatively key problem. High-speed spray is an effective method which can fully mix the extracting agent and the crude GeCl4. The experiments prove that the quantity of low-resistance germanium ingots can